Study on Agronomic Evaluation of Tomato (Lycopersicon Esculentum, Mill.) Varieties for Phonological, Growth and Yield Characters - Gebremeskel, Haileslassie; Abebe, Haile; Biratu, Wakuma; Jaleto, Kedir (Current Research in Agricultural Sciences, 2016)
The field experiment was carried out at the research station of Mehoni Agricultural Research Center, Fachagama, Ethiopia in 2013 and 2014 cropping season under irrigation and in 2014 for rain fed experiment only. The experiment consisted of four commercial tomato varieties arranged in a completely randomized block design with four replications. In the 2013 cropping season, days to 50% flowering and maturity, plant height, fruit length, fruit diameter, number of fruits per plant, marketable yield, unmarketable yield and total yield were significantly influenced by varietal difference. Likewise, it was also observed that variety exerted a significance effect on establishment percentage, days to 50% maturity, plant height, number of fruits/plant and marketable yield under both irrigation and rain fed and on unmarketable yield under irrigation conditions of the 2014 cropping year. Under irrigation, the highest marketable yield (414.58 q ha-1) was obtained at Chali variety followed by Miya variety (289.17 q ha-1) in 2014 while the lowest value (110.83 q ha-1) was obtained from Melka sholla in the 2013 cropping season. Whereas the highest (295.58 q ha-1) and lowest marketable yields (283.33 q ha-1) were observed at Chali and Melksa sholla varieties under rain fed condition of the 2014 cropping season.